Física e segurança no trânsito: uma proposta didática por uma professora iniciante - Back, Susana (2013)
The present work had to educational resources for the Teaching of Physics in the present research papers/teatching/extension education in the field of Science/ Physics/Teaching in the production of educational material with a view to developing awareness of students in relation to them traffic safety as well as enhance the teatching practice, developing a beginning teacher in the habit of reflection. Therefore we created a didactic proposal consists of seven units with a view to teaching content related to quantity of motion, momentum, work, energy and Newton s laws using teatching resources the development of various activities that comprise these units. All lessons were recorded in daily teatching practice, wich were subsequently analyzed with the activities undertaken by the students. We conducted a survey which conceptual content, didactic proposal, as well as skills (PCN+). Stands out the paper that planning has in teaching practice because, it is through this that you plan and anticipate the actions that will be developed in the classroom. In relative reflection of teaching practice of beginning teacher, it is believed that this was achieved. It is clear that most of the activities was possible to develop a set of conceptual content, procedural and attitudinal, and this should be thought of all classes, because then the teacher is able to leverage its role in forming citizens. In relation to student s learning, there is an evolution of their knowledge of physics so that it is clear that at the beginning only demonstrated familiarity with kinematics and after out of momentum, Newton s first law and force, who were content more closely related to traffic safety issue, and also Newton s third law and energy. Regarding the awareness of students about safety, it was hoped that the posters mode by them appear more physical content, but what stood out was the use of Newton, which is related to the use of seat belts. This can be explained by familiarity with this issue.